Efficacy of Preharvest Calcium Chloride and Calcium Gluconate Treatments on the Postharvest Quality Maintenance of Marian Plums During Shelf Life - Li, Da; Sunthusamran, Sirima; Youryon, Pannipa; Bo, Wen; Supapvanich, Suriyan; Techavuthiporn, Chairat (My University, 2026)
Marian plum is a commercial fruit that deteriorates rapidly during storage. The effects of preharvest treatment with calcium chloride (CaCl₂) and calcium gluconate (CaGlu) at two concentrations (1 and 2%) on maintaining the postharvest quality of marian plum during shelf life at 26±2ºC were investigated. The fruits were sprayed with both calcium salts 2 days prior to harvest. The outcomes show that both the CaCl2 and CaGlu treatments preserved fruit visual appearance and postponed color development during shelf life. No fruit rot incidence appeared on the 2% CaCl2 and 2% CaGlu treated fruits during storage for 8 days. All calcium treatments retarded the increase in weight loss compared to the untreated fruits. The fruit firmness was maintained by the calcium treatments, and 2% CaGlu treatments improved the firmness greater than other treatments. Moreover, the increases in malondialdehyde (MDA), total soluble solids (TSS) and BrimA, as well as the decreased total acidity (TA) were lowered by the calcium treatments. The total phenols and antioxidant capacities, including ferric reducing antioxidant power (FRAP) and DPPH free radical scavenging activity, were enhanced by the calcium treatments. In correlation analysis, the firmness showed significantly negative correlation with MDA and parameters related to ripening. Moreover, the MDA had significant negative correlation with DPPH radical scavenging activity. The softening of the marian plum was closely related to membrane degradation. Both preharvest CaGlu and CaCl2 treatments at 2% are feasible approaches to preserve the postharvest quality of marian plums during shelf life at room temperature.
Keywords: calcium chloride; calcium gluconate; marian plum; postharvest quality